Transfer Teknologi Budidaya Ikan Nila Monoseks Jantan Desa Lalonggolosua Kabupaten Kolaka Melalui Kegiatan Kosabangsa - Rahim, Rahim; Bahari, Doddy Ismunandar; Pariakan, Arman; Erfina, Erfina; Irmawati, Irmawati; Fakhriyah, Sitti; Aslamyah, Siti; Kamaruddin, Kamaruddin (Universitas Mataram, 2025)
The Kosabangsa program aims to develop and apply science and technology resulting from university research to meet the needs and improve the community's welfare. Through this Kosabangsa program, the implementation team and the assistance team collaborated to apply seed production methods and technology for male monosex tilapia cultivation in brackish water ponds of the Lalonggolosua Village Pond Farmer Group, which was the target partner and beneficiary. The problem faced by partners is the decline in pond production due to the failure of vaname shrimp farming so a commodity is needed to reinvigorate fish farming in ponds. One of these commodities is male monosex tilapia because it has a high growth rate, can adapt well to brackish salinity, and prevents unwanted reproduction during the cultivation process. The stages of the Kosabangsa activity of male monosex tilapia farming technology consist of several stages, namely, the transfer of knowledge from the mentoring team to the implementation team, training and mentoring, and evaluation of activities. The results of Kosabangsa activities for approximately three months (September - December 2023) are that partners have applied the technique of installing tarpaulin ponds used for enlargement of prospective broodstock and seed production, application of wild honey for male monosexed seed production, and have applied the male monosexed tilapia enlargement method in partner farms.